1986
DOI: 10.1128/jb.168.3.1128-1132.1986
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the penicillinase repressor gene penI of Bacillus licheniformis and regulation of penP and penI by the repressor

Abstract: Bacillus licheniformis penicillinase genes, penP and penl, are coded on a 4.2-kilobase EcoRI fragment of pTTE21 (T. Imanaka, T. Tanaka, H. Tsunekawa, and S. Aiba, J. Bacteriol. 147:776-186, 1981). The EcoRI fragment was subcloned in a low-copy-number plasmid pTB522 in Bacillus subtilis. B. subtilis carrying the recombinant plasmid pPTB60 (Tcr penP+ penI+) was chemically mutagenized. Of about 150,000 colonies, two penl(Ts) mutant plasmids, pPTB60D13 and pPTB60E24, were screened by the plate assay at 30 and 48°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…DNase I footprinting analysis of BlaI binding to a DNA fragment containing both promoters confirmed that site-specific DNA binding is localized to the regions of dyad symmetry contained within the promoter regions of blaI and blaP ( fig.4), as previously predicted [5]. Footprinting of the complementary strand and DNA containing the isolated promoters revealed similar protected regions (not shown).…”
Section: Footprinting Analysissupporting
confidence: 83%
See 2 more Smart Citations
“…DNase I footprinting analysis of BlaI binding to a DNA fragment containing both promoters confirmed that site-specific DNA binding is localized to the regions of dyad symmetry contained within the promoter regions of blaI and blaP ( fig.4), as previously predicted [5]. Footprinting of the complementary strand and DNA containing the isolated promoters revealed similar protected regions (not shown).…”
Section: Footprinting Analysissupporting
confidence: 83%
“…The gene encoding the repressor (blaI) has been cloned from Bacillus licheniformis 749 and from a closely related strain 9945A and has been shown to lie 5' to blaP [4,5]. Transcriptional analysis [6] demonstrated that blaI mRNA is transcribed divergently from blaP mRNA and that it is coinduced with blaP mRNA, suggesting that blair expression is autoregulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same areas also contained promoter-like and Shine-Dalgarno (SD)-like sequences in opposite directions followed by a start codon for another open reading frame. This open reading frame extended for at least 250 bp in MRSA PBP (only 32 bp being shown in fig.l Bacillus licheniformis [12] and is supposed to be involved in regulation of these inducible ,&-lactamase genes.…”
Section: Resultsmentioning
confidence: 99%
“…1 [6,7]). The N-terminal half of CopY shows 30% sequence similarity to the bacterial repressors of ß-lactamases, PenI, of Bacillus licheniformis [8] and related proteins and probably corresponds to the domain that recognizes the DNA promoter sequences [9]. The C-terminal region of CopY harbors a CxCxxxxCxC metal-binding motif.…”
Section: Introductionmentioning
confidence: 99%